Pembangunan Aplikasi Program Membership Wahana Go-Kart menggunakan Flutter dengan Pustaka Deepface (Studi Kasus CV Indi Karya Teknik) - Jemal Rashidi; Komang Candra Brata; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Batu City feels tight competition in the tourism industry as one of the tourist cities in East Java Province. As a token of appreciation for their loyalty to an organization or company, loyalty programs provide benefits or perceived value by members. As a company engaged in the tourism industry, especially in the Go Kart business in Batu City, East Java, CV Indi Karya Teknik implements and offers program membership services to their customers at their ride agency called Indigokart Indonesia. The implementation of the Indigokart Indonesia membership program has faced challenges in the form of cases of membership cards changing hands from card owners to their acquaintances, losing membership cards, and forced membership program members with tickets at normal prices, not at membership promo prices. CV Indi Karya Teknik requires an approach or substitute for implementing a membership card-based membership program as a solution for implementing their loyalty program. The use of mobile device technology and facial recognition technology can be used as a solution to solve the problem of implementing the Indigokart Indonesia loyalty program. the existence of the results of this study, changed the basis of the Indigokart Indonesia game vehicle membership program from membership card-based to facial recognition-based.